BUILDING CLIMATE CHANGE ADAPTABILITY THROUGH INTEGRATING INDIGENOUS AND SCIENTIFIC KNOWLEDGE SYSTEMS IN LESOTHO - Alouis Chilunjika (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2024)
Climate change as a human security threat has weakened the ability of states to deal with severe weather patterns, droughts, land degradation, flooding, and other climate-related changes. This has significantly affected poor communities in developing countries as they are prone to low precipitation, high temperatures, and high poverty levels. In light of this, communities in Lesotho have for generations been adapting to climate induced hazards and risks by developing situation specific livelihood practices and building resilience of their households and communities. Nonetheless, in recent years, the increasing intensity and frequencies of climate extremes have revealed the limitations of indigenous and local knowledge in dealing with the scourge of climate change. As such, the need for the integration of indigenous and scientific knowledge systems in coping with and adapting to climate change. The study being qualitative in nature relied on the extensive review of purposively selected written sources which include journal articles, books, book chapters, Government publications, newspapers, magazines as well as a Key Informant interview to collect data which was analysed using thematic and content analysis techniques. The study established that, integrating traditional and scientific knowledge systems in dealing with climate change vulnerability and impacts in Lesotho is critical for policy makers to develop multi-level, multi-dimensional, multi-hazard and multi-disciplinary adaptation and resilience-building strategies and solutions that are sustainable, cost-effective and participatory. The integration of the scientific and indigenous knowledge and practices will help in proactively identifying current and future risks and hazards thus enabling the better implementation of climate-change policies in Lesotho.